PETROLEUM REFINING IN NONTECHNICAL LANGUAGE - Leffler, William L. (PennWell, 2020)
For 45 years, William Leffler's Petroleum Refining in Nontechnical Language has been the go-to best seller for anyone needing to know the fundamentals of refining. Fluid prose, easy-to-understand graphics, and helpful analogies (like the "beer bottle principle") make the refining processing schemes clear. Each chapter was carefully written in nontechnical language to give the reader a basic understanding of the refining industry. The book can be used for self-study, as a classroom textbook, or as a quick reference.As always, Leffler's classic unit-by-unit description follows the oil molecules from the oil patch through the refinery to the consumer. In this edition, the industry's technologic progress is brought up to date. In addition, Leffler adds a new chapter on the impact of hydraulic fracing on oil price setting in refining markets and another on competitive positioning.